Digital Professional Learning Networks and the Construction of Professional Identity Among Preservice EFL Teachers: A Qualitative Inquiry - Try Mahendra Siregar; Rahmat Sapaat Siregar (Barkah Publishing, 2026)
This qualitative study examined how engagement with digital Professional Learning Networks (PLNs) shapes the professional identity construction of preservice English as a Foreign Language (EFL) teachers. Framed within Wenger’s Communities of Practice theory and Vygotskian sociocultural principles, the research addressed a critical gap concerning the social-epistemological mechanisms through which informal, digitally-mediated networks contribute to identity formation during initial teacher education. Participants were 18 final-year preservice EFL teachers who actively participated in digital PLNs across multiple platforms (Twitter/X, Instagram, Facebook groups). Data comprised semi-structured interviews, reflective journals, and digital artefacts (screenshots of networked interactions). Thematic analysis generated three overarching themes: (1) digital legitimate peripheral participation – characterised by gradual shifts from observation to contributive engagement; (2) resonant resource ecologies – participants’ curation of personalised content streams that affirmed emergent pedagogical selves; (3) identity dissonance and negotiation – tensions encountered when digital PLN narratives contradicted institutional placement realities. Findings underscore that digital PLN engagement enables preservice EFL teachers to rehearse professional identities, access diverse communities of practice, and negotiate between aspirational and enacted selves. However, identity dissonance emerged as a consequential phenomenon when digitally-internalised professional discourses encountered traditional school micro-politics. The study concludes that teacher education programmes must explicitly scaffold critical digital PLN participation, fostering reflective meta-awareness of how networked interactions mediate teacher identity development.